Ten Types of Innovation: The Discipline of Building Breakthroughs - Kovidvisith, Kalaya (Journal of Architectural/Planning Research and Studies (JARS), 2022)
The attempt to bring innovation into practiceis the key to sustainable growth of organizations. Fordecades, innovation strives to challenge outdatedsolution and design new ventures that can adapt tothe new realities. Many models have been proposedyet some are too difficult to follow and barely survivedthrough resistance. After a long gestation period,Larry Keeley, a world famous innovation consultant,and his colleagues have successfully simplifiedtheir practice and research into The Ten Type ofInnovation. Unlike others, the author uses thestorytelling method to expose the industry patternsthat happen in the three decades of research.The ten distinct types of innovation will help to laythe comprehensive outline for the entrepreneursto develop their own innovation culture withinorganization.